SURVEI MINAT SISWA TERHADAP KEGIATAN EKSTRAKURIKULER BOLAVOLI DI SMPN I SUNGGUMINASA KABUPATEN GOWA - Ramli, Ramli (UNIVERSITAS NEGERI MAKASSAR, 2020)
This study aims to find out about students' interest in the volleyball extracurricular activities at SMP Negeri I Sungguminasa, Gowa Regency. This research is a descriptive study with a single variable. The sample used in this study were all students who took extracurricular activities in volleyball as many as 40 people. Data collection techniques using a questionnaire. Furthermore, the data obtained were analyzed using descriptive analysis of percentages with the help of a computer through the SPSS 20.00 program. The results of this study indicate that students' interest in volleyball extracurricular activities in Sungguminasa Junior High School I students in Gowa Regency is relatively high with a percentage reaching 64.81% which is influenced by several indicators of interest, such as: motivation and ideals, attitudes towards teachers and lessons, support family, facilities and others. The conclusion that can be drawn from the results of this study is that students already have a high interest with the percentage of SS 26.225%, S 38.29%, TS 26.29%, STS 8.90% towards volleyball in students of Junior High School Sungguminasa, Gowa Regency.